Epidemiological and clinical features of Panton-Valentine Leukocidin positive Staphylococcus aureus bacteremia: A case-control study. - Ming Da Qu; Humera Kausar; Stephen Smith; Peter G Lazar; Aimee R Kroll-Desrosiers; Carl Hollins; Bruce A Barton; Doyle V Ward; Richard T Ellison (PLoS ONE, 2022)
Background Panton-Valentine Leukocidin (PVL) toxin in Staphylococcus aureus has been associated with both severe pneumonia and skin and soft tissue infections. However, there are only limited data on how this virulence factor may influence the clinical course or complications of bacteremic S. aureus infections. Methods Between September 2016 and March 2018, S. aureus isolates from clinical cultures from hospitals in an academic medical center underwent comprehensive genomic sequencing. Four hundred sixty-nine (29%) of 1681 S. aureus sequenced isolates were identified as containing the genes that encode for PVL. Case patients with one or more positive blood cultures for PVL were randomly matched with control patients having positive blood cultures with lukF/lukS-PV negative (PVL strains from a retrospective chart review). Results 51 case and 56 control patients were analyzed. Case patients were more likely to have a history of injection drug use, while controls more likely to undergo hemodialysis. Isolates from 78.4% of case patients were methicillin resistant as compared to 28.6% from control patients. Case patients had a higher incidence of pneumonia and skin and soft tissue infection and longer duration of fever without differences in length of bacteremia. Clinical cure or expiration was comparable. Conclusions These results are consistent with prior observations associating the PVL toxin with both community-acquired MRSA strains as well as severe staphylococcal pneumonia. The presence of the PVL toxin does not appear to otherwise influence the natural history of bacteremic S. aureus disease other than in prolonging the duration of fever.